2011
DOI: 10.1021/cm103571y
|View full text |Cite
|
Sign up to set email alerts
|

Controlling Zeolitic Imidazolate Framework Nano- and Microcrystal Formation: Insight into Crystal Growth by Time-Resolved In Situ Static Light Scattering

Abstract: We report on a simple and straightforward method that enables the rapid room-temperature production of nanocrystals (finely tuned in size between ∼10 and 65 nm) and microcrystals (∼1 μm) of the prototypical microporous zeolitic imidazolate framework (ZIF) material ZIF-8. Control of crystal size is achieved in a novel approach by employing an excess of the bridging bidentate ligand and various simple auxiliary monodentate ligands with different chemical functionalities (carboxylate, N-heterocycle, alkylamine). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

50
691
4
4

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 818 publications
(749 citation statements)
references
References 61 publications
50
691
4
4
Order By: Relevance
“…Notably, the shortest synthesis time in our strategy was only 1 min at RTP, whereas conventional solvothermal methods require a synthesis time of 24 h at HTP [18], demonstrating that organic amines play a significant role in accelerating the formation of ZIF-8. Gross et al [23], Nordin et al [24], and Cravillon et al [25] also reported that ZIFs could be synthesized within 10 min at RTP by using an organic amine (triethylamine) as a protonation agent, indicating that the organic amine (e.g., diethanolamine) used in this work acts as a protonation agent. However, the ZIFs synthesized with triethylamine as a protonation agent only possessed microporous structures instead of hierarchical porous structures.…”
Section: Science China Materialsmentioning
confidence: 64%
See 2 more Smart Citations
“…Notably, the shortest synthesis time in our strategy was only 1 min at RTP, whereas conventional solvothermal methods require a synthesis time of 24 h at HTP [18], demonstrating that organic amines play a significant role in accelerating the formation of ZIF-8. Gross et al [23], Nordin et al [24], and Cravillon et al [25] also reported that ZIFs could be synthesized within 10 min at RTP by using an organic amine (triethylamine) as a protonation agent, indicating that the organic amine (e.g., diethanolamine) used in this work acts as a protonation agent. However, the ZIFs synthesized with triethylamine as a protonation agent only possessed microporous structures instead of hierarchical porous structures.…”
Section: Science China Materialsmentioning
confidence: 64%
“…The particle size of ZIF-8_A1 is considerably smaller than that of a previous ZIF-8 sample synthesized with triethylamine within 10 min (~100 nm) or C-ZIF-8 ( Fig. S1), [18,23] which can be attributed to fast nucleation (< 1 min) between deprotonated ligands and metal ions, resulting in the formation of small nanocrystals [23,25]. Furthermore, the apparent voids surrounded by the walls consisting of nanoparticles ( Fig.…”
Section: Morphologies Of Hierarchical Porous Zif-8mentioning
confidence: 73%
See 1 more Smart Citation
“…Parallel work of Cravillon et al have observed that in room-temperature syntheses cube-shaped crystals ({100} crystal form) first develop in early stages and eventually transform into rhombic dodecahedra ({110} crystal form). 44 The polyhedron (crystallographic point group symmetry 43m) consists of 12 rhombic faces perpendicular to AE110ae. When viewed along the AE100ae direction, one out of six corners is seen that lay on a 4-fold rotation axis (Figure 7b, upper left).…”
Section: Chemistry Of Materialsmentioning
confidence: 99%
“…Compared with singleangle setups, where assumptions about the morphology and size distribution of the particles are necessary to extract structural parameters, multiangle light scattering permits reliable extraction of the molecular weight (M w ), radius of gyration (R g ), and hydrodynamic radius (R H ) without specific assumptions about the shape and the degree of polydispersity of the particles, as previously demonstrated for the aggregation of dyestuff molecules and for nucleation and growth of silica particles (27,28). Application of this in situ technique provides us with a consistent set of M w , R g , and R H of assembling filaments and enables us to follow quantitatively and in real time the longitudinal growth of ULFs toward filaments of lengths up to 600 nm.…”
Section: Significancementioning
confidence: 99%